Efficient removal of heavy metals by synergistic actions of microorganisms and waste molasses. (April 2020) - Sun, Yan; Lan, Jirong; Du, Yaguang; Li, Zhuang; Liao, Xi; Du, Dongyun; Ye, Hengpeng; Zhang, Tian C.; Chen, Shaohua
Graphical abstract: Highlights: As a carbon source, molasses was also used as an adsorbent and reductant. The removal efficiencies of Zn(II), Cr(VI), Cd(II), and Cr(total) were above 90%. The removal path of heavy metals and the contribution of each path were elucidated. Abstract: In this study, two bacteria strains ( Enterobacter sp. SL and Acinetobacter sp. SL-1) and waste molasses (carbon source) were used to remove Zn(II), Cd(II), Cr(VI), and Cr(Total) in the liquid solution (87 mg·L). The results showed the removal efficiencies of Cr(Total) and Cr(VI) could reach over 98.00% after reaction, and the removal efficiencies of Zn(II) and Cd(II) were all about 90.00% by the synergistic actions of microorganisms and waste molasses. In this process, waste molasses provides nutrients for microorganisms and has the characteristics and capability of Cr, Zn, and Cd. Microorganisms mainly use biological adsorption (36.95% and 45.69%) and metabolism (24.37% and 17.05% by producing humic-acid and fulvic-acid like substances) to remove Zn(II) and Cd(II), while waste molasses could to remove Cr(Total) (81.24%) and Cr(VI) (75.90%). This study has potential application value for the treatment of wastewater containing high concentrations of heavy metals.